management perspective in the supply chain of services in the tourism sector (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
The purpose of this article is to provide an overview of the evolution of supply chain management in the tourism and hospitality sector. It starts from general concepts until arriving at the analysis of the supply chain of services in the tourism and hotel sector. It is a qualitative and transactional research, in this study information was searched in databases and relevant articles published between 2016 and 2022 were chosen for analysis. From this review, it was observed that good communication in the supply chain contributes to reducing costs and improving the flow of information between the actors in the chain. This is a methodological review of supply chain research in service supply management, service demand management, service integration management, and service coordination management, by categorizing the literature reviewed and the status of each investigation. The main findings show that in the reviewed literature the evolution of the supply chain and the studies that contribute to a better administration to improve the structuring of the processes are appreciated. Therefore, this article integrates background, trends and theories applied in the supply chain of hotel services and tourism.
Keywords: Supply chain management; hospitality; services; tourism